Das ruas às organizações: emergência e consolidação da militância à direita em Sergipe - Santos, Adrielma Silveira Fortuna dos (2021)
This dissertation analyzes the arising of right-wing social movements and the organization of protests event by them in the Sergipe state, between 2014 and 2019. It contributes with a more comprehensive discussion that focuses on social movements and their dynamics of organization and performance as being a starting point to investigate who are the social actors that build these movements, what are your previous social networks, what are the alliances, the conflicts and the strategies uses in different political field. Thus, the logics of organization, entry and the action ways that these movements and the actors on the right-wing around the three main political field were analyzed: the street, the university and the elections. Consequently, making use of concepts and analyses that seek to account for macro, meso and micro sociological aspects that involves our main theme. The methodological procedures consisted on: the ethnography of protests events; in the survey of information regarding the appearance of the right-wing social movements and its elements that forms the protest event (place, actors, complaints, repertoires, etc.), using as source electronic newspapers, the participant observations and the social media of some persons from specific right-wing social movements. This survey resulted in the construction of a database with the register of 140 protests events; the analyses of the socialization spaces, the previous social networks, the social, political, and activist profile of 28 leaderships, through semi-structured interviews. Based on the results that were found, the dissertation we stand by is that the emergence and consolidation of the right wing social movements in Sergipe between 2014 and 2019 it was only possible due to the articulation of three factors: a favorable political context, which gave the opportunity for the entrance of new actors in the institutional and associative politics; communication resources of lower-costs and long-range, specially Facebook and WhatsApp, which reduced the risks of individual engagement in the social movements and protests events; finally, the biographical disposition and previous relations network, that allowed the construction of a right-wing collective identity and a feeling of belonging to the group, as well as it contributed to the creation and sustainability of the first movements. The results showed that the field of right wing movements it is characterized by the ideological overlap, by the plurality and fragmentation; that the virtual social networks, networks previous relationships of certain leaderships, as well as the supporters and sponsors network were fundamental for both creation and sustainability of the right-wing movements in Sergipe; the results indicated that the demonstrations of June 2013, the 2014, 2016 and 2018 elections, were events which generated opportunities, objective and symbolic conditions for the organization of those social movements in question. In that way, we hope our research has evidenced the local dynamics of performance of the social movements analyzed and this contributes to comparative analysis and so that other researchers have curiosity and interest in the theme still to be studied.